Mineralogy of Deep-Sea Manganese Nodules and Advances in Extraction Technology of Valuable Elements from Manganese Nodules - Xu Wang; Wenqing Qin; Maolin Li; Xueduan Liu; Yangrui Cheng; Shiping Chen; Congren Yang (Metals, 2024)
The vast seabed holds tremendous resource potential that can provide necessary materials for future human societal development. This study focuses on the mineralogy of seafloor manganese nodules off the coast of China in the Western Pacific and the primary techniques for extracting valuable metal elements from manganese nodules. The research indicates that the main valuable metal elements in the manganese nodules from this region include Cu, Co, Ni, Mn, Fe, etc. The key to extracting these valuable metals lies in reducing Mn(IV) to Mn(II) to disrupt the structure of the nodules, thereby releasing the valuable elements. The extraction processes for the main valuable metal elements of manganese nodules are mainly divided into two categories: pyrometallurgical–hydrometallurgical and solely hydrometallurgical. In order to cope with the challenges of environmental change and improve utilization efficiency, bioleaching, hydrogen metallurgy, and co-extraction are gaining increasing attention. For promoting commercialization, the future development of manganese nodule resources can refer to the technical route of efficient short-process extraction technology, the comprehensive recovery of associated resources, and tail-free utilization.